2023 updated MASCC/ESMO consensus recommendations: prevention of radiotherapy- and chemoradiotherapy-induced nausea and vomiting - Ruhlmann, Christina H.; Jordan, Karin; Jahn, Franziska; Maranzano, Ernesto; Molassiotis, Alex; Dennis, Kristopher (Supportive care in cancer, 2023)
Radiotherapy and chemoradiotherapy-induced nausea and vomiting (RINV and C-RINV) are common and distressing, and there is a need for guidance for clinicians to provide up to date optimal antiemetic prophylaxis and treatment. Through a comprehensive review of the literature concerning RINV and C-RINV, this manuscript aims to update the evidence for antiemetic prophylaxis and rescue therapy and provide a new edition of recommendations for the MASCC/ESMO antiemetic guidelines for RINV and C-RINV.